Is foam rolling as effective as its popularity suggests? A randomised crossover study exploring post-match recovery in female basketball - Pernigoni, M.; Kreivyte, R.; Lukonaitiene, I.; Toper, C. R.; Kamandulis, S.; Conte, D. (Journal of Sports Sciences, 2023)
This study aimed to assess the effectiveness of foam rolling as a post-match recovery tool in basketball. Using a crossover design, 13 female players completed two simulated matches, followed by foam rolling (FR) or placebo (CON). Countermovement jump height (CMJ), heart rate variability (Ln-rMSSD), muscle soreness (VAS), perceived recovery (TQR) and fatigue (Rating-of-Fatigue) were recorded at pre-match, post-match, post-recovery and 24 h post-match. No significant effect of time*intervention and intervention were found for any variable (p > 0.05), while a significant effect of time (p < 0.01) was reported for all variables. Post-hoc analyses revealed lower CMJ and Ln-rMSSD at post-match compared with all other time points (p < 0.001), increases in pre-match VAS scores at all subsequent time points (p < 0.01), and worse TQR and Rating-of-Fatigue scores from pre-to-post-match and pre-match-to-post-recovery (p < 0.01), except for unchanged TQR values from pre-match-to-post-recovery in FR (p > 0.05). Overall, the present data suggest that foam rolling was generally ineffective for improving post-exercise recovery in female basketball players after a single match. Future research investigating the effectiveness of foam rolling in players of different sex, age and/or competitive level is warranted to provide further insight on the topic.